2019
DOI: 10.2141/jpsa.0180024
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Biomarker Amino Acids and Neuropeptide Afford Thermotolerance in Chicks

Abstract: With global warming, heat stress is becoming a pressing concern worldwide. In chickens, heat stress reduces food intake and growth, and increases body temperature and stress responses. Although it is believed that young chicks do not experience heat stress as they need a higher ambient temperature to survive, our series of studies in young chicks showed that they are sensitive to heat stress. This review summarizes current knowledge on amino acid metabolisms during heat stress, with special emphasis on the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 113 publications
0
18
1
Order By: Relevance
“…At hatching, RT was clearly reduced in the high-dose group (p<0.01) compared with control chicks (Figure 1A). It has been reported that TM-dependent lower RT occurred at hatching due to a lower metabolic rate before hatching [18], which resulted from a feedback of higher metabolic rate under TM during embryogenesis [9]. Previously, we found that in ovo administration of L-Leu on ED 7 stimulated metabolic activity and lipid metabolism during the middle stages of embryogenesis [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At hatching, RT was clearly reduced in the high-dose group (p<0.01) compared with control chicks (Figure 1A). It has been reported that TM-dependent lower RT occurred at hatching due to a lower metabolic rate before hatching [18], which resulted from a feedback of higher metabolic rate under TM during embryogenesis [9]. Previously, we found that in ovo administration of L-Leu on ED 7 stimulated metabolic activity and lipid metabolism during the middle stages of embryogenesis [8].…”
Section: Discussionmentioning
confidence: 97%
“…Some free amino acids are recognized as biomarkers of heat stress, since they are significantly affected by heat stress [3,4]. These free amino acids play critical roles in thermoregulation, as well as in reducing body temperature in chicks under heat stress [59].…”
Section: Introductionmentioning
confidence: 99%
“…High environmental temperatures, especially combined with high humidity, impose severe stress on broiler health and welfare due to poor heat tolerance, with a limited ability to regulate heat loss by feathering and without sweat glands. All these pathophysiological changes negatively affect production performance, accelerate morbidity and mortality, and cause heavy economic losses [ 89 , 90 ]. Excessive mortality due to heat stress is commonly seen in commercial broiler flocks.…”
Section: Heat Tolerance and Heat Stress In Commercial Broilersmentioning
confidence: 99%
“…Modern broiler chickens have been selected continuously for maximum growth rate and high feed conversion efficiency over 6-8 weeks [2], by which the breeding program affects broiler biological homeostasis, resulting in immature or impaired metabolism, immunity, and antioxidant status, as well as susceptibility to inflammation and infection. All these changes affect production performance negatively, accelerate mortality and morbidity, and consequently cause heavy economical losses [3,4]. Excessive mortality due to HS is commonly seen in commercial flocks of broilers.…”
Section: Introductionmentioning
confidence: 99%